Relationship between Oil Exports, Renewable Energy Consumption, Agriculture Industry, and Economic Growth in Selected OPEC Countries: A Panel ARDL Analysis - Aidarova, Aina B.; Mukhamediyeva, Gulzada; Yessentayeva, Aizhan A.; Utemissova, Guliya; Tastanbekova, Karlygash; Mustafayeva, Bagila; Myrzabekkyzy, Kundyz (International Journal of Energy Economics and Policy, 2024)
This study uses the panel ARDL method to analyze the relationship between oil exports, renewable energy consumption, agricultural industry, and economic growth in selected OPEC member countries. The study examined data from 9 OPEC countries from 1990 to 2024. The findings showed that while oil exports in OPEC countries have a positive long-term effect, they have a negative short-term impact in Nigeria and a positive short-term impact in other countries. The consumption of renewable energy has been found to have a negative long-term effect. However, the short-term impact varies from country to country, with the observation that the short-term effect is insignificant in most countries. The long-term effect of the food production index is statistically insignificant. On the other hand, the short-term effect varies significantly among countries, with a notable negative impact in some countries. Notably, Equatorial Guinea stands out from other variables, as all variables have insignificant effects in the short term. Research findings have demonstrated that oil exports play a supportive role in the economic growth of OPEC countries.